EP635 Minimizing the dose of oral megestrol in combination with the levonorgestrel-releasing intrauterine device: an equally effective approach for the conservative management of atypical hyperplasia and well differentiated endometrial carcinoma. (1st November 2019) - Haidopoulos, D; Rountis, A; Pergialiotis, V; Theodoulidis, V; Thomakos, N; Loutradis, D; Rodolakis, A
Abstract : Introduction/Background: The purpose of the present study is to evaluate the efficacy of the combination of low dose megestrol acetate (MA) (80 mg/day) and the levonorgestrel-releasing intrauterine device (LNG-IUD) for the treatment of complex atypical hyperplasia (CAH) and low-grade endometrial adenocarcinoma (EC) in premenopausal women, 45 years old or younger, who desire to preserve their fertility. Methodology: A retrospective study that included a consecutive series of patients of reproductive age who were treated conservatively with the combination of per os MA (80 mg/day) and the LNG-IUD for CAH and grade I endometrioid EC. The response rate for each of the two conditions was monitored following a 6-month period of treatment. Results: Twenty-two patients were diagnosed with CAH or grade I endometrioid EC. Eighteen of them were evaluable at the 6-month study point. Among them, 5 patients (27.8%) had an initial diagnosis of CAH and the other 13 (72.2%) were diagnosed with grade I endometrioid EC. Overall, the response rate was 77.7% at the 6-month evaluation exam (80% for the CAH group and 76.9% for the grade I endometrioid EC). Conclusion: The concomitant use of low-dose MA orally and the LNG-IUD seems to be an efficient option for the conservative treatment of CAH or early- grade EC in young women who wish to preserve their fertility. Future studies should provide head to head comparison with systemic progestin therapy to corroborate our findings. Disclosure: Nothing to disclose.